2013
DOI: 10.1097/ccm.0b013e31826ab3a1
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Excursions Below the Cerebral Autoregulation Threshold During Cardiac Surgery are Associated With Acute Kidney Injury*

Abstract: Objectives To determine whether mean arterial blood pressure (MAP) excursions below the lower limit of cerebral blood flow (CBF) autoregulation during cardiopulmonary bypass (CPB) are associated with acute kidney injury (AKI) after surgery. Setting Tertiary care medical center. Patients Four hundred ten patients undergoing cardiac surgery with CPB. Design Prospective observational study. Interventions None. Measurements and Main Results Autoregulation was monitored during CPB by calculating a continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
146
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 179 publications
(157 citation statements)
references
References 27 publications
(47 reference statements)
5
146
1
5
Order By: Relevance
“…Therefore, the authors' observation that serum creatinine elevation was associated with higher mortality should not be surprising [5]. Nevertheless, despite these limitations, this study is an extension of previously published evidence that cerebral perfusion and GFR are interconnected, with patients who experience cerebral hypoperfusion at an increased risk of renal injury and vice versa, with subsequent effects on outcome and mortality [6,7]. Without a larger study, control population, or similar validation, the clinical impact of this study remains to be seen outside the realm of physiological insights.…”
mentioning
confidence: 62%
“…Therefore, the authors' observation that serum creatinine elevation was associated with higher mortality should not be surprising [5]. Nevertheless, despite these limitations, this study is an extension of previously published evidence that cerebral perfusion and GFR are interconnected, with patients who experience cerebral hypoperfusion at an increased risk of renal injury and vice versa, with subsequent effects on outcome and mortality [6,7]. Without a larger study, control population, or similar validation, the clinical impact of this study remains to be seen outside the realm of physiological insights.…”
mentioning
confidence: 62%
“…Even though the surgical team was blinded to the LLA measurements, they could have chosen a higher MAP for patients on bypass who subjectively appeared to have an altered LLA, such as those who had hypertension that was difficult to control intraoperatively or those who appeared frail. Prior studies have shown that the duration and magnitude of BP below the LLA is associated with acute kidney injury38 and major morbidity and mortality2 after cardiac surgery. Those studies suggested that maintaining MAP within the range of cerebral autoregulation may improve postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Innovative technology to determine the lower limit of the cerebral autoregulation threshold has been developed and validated at Hopkins. Excursions of MAP below the lower limit of cerebral autoregulation were independently associated with AKI [28]. Because of this, observations of cerebral perfusion may be used as a surrogate for renal perfusion.…”
Section: Novel Strategies At Detectionmentioning
confidence: 99%